A Serious Game: Performance Management in Italian Ministries. Issue 9 (29th July 2017) - Rebora, Gianfranco; Ruffini, Renato; Turri, Matteo
ABSTRACT: In 2009, extensive performance management measures were introduced in Italian ministries, following a significant legislative initiative. The objectives that were initially set, however, have not yet been reached. In the paper, the authors discuss this issue, starting with the consideration of the main limits on the introduction of performance measurement systems in public organizations. The discussion leads to the conclusion that the shortcomings of performance management depend not only on the persistence of an administrative paradigm, but also on the underestimated impact of control over organizational behavior; where the latter is linked not to mechanical logic processes, but to more sophisticated forms of reactivity or even counter-intuitive sense-making processes.